Ey let me change the title god damn it

From testwiki
Revision as of 06:40, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


Notation
1.1 Special Notation
Areas
1.2 Elementary Algebra
1.3 Determinants
1.4 Calculus of One Variable
1.5 Calculus of Two or More Variables
1.6 Vectors and Vector-Valued Functions
1.7 Inequalities
1.8 Fourier Series
1.9 Calculus of a Complex Variable
1.10 Functions of a Complex Variable
1.11 Zeros of Polynomials
1.12 Continued Fractions
1.13 Differential Equations
1.14 Integral Transforms
1.15 Summability Methods
1.16 Distributions
1.17 Integral and Series Representations of the Dirac Delta



DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
4.4.E1 ln 1 = 0 1 0 {\displaystyle{\displaystyle\ln 1=0}} - Mit Item:QID
\ln@@{1} = 0

ln(1) = 0
Log[1] == 0
Successful Successful - Successful [Tested: 1]
4.4.E1 ln 1 = 0 1 0 {\displaystyle{\displaystyle\ln 1=0}} - Mit Math-QID
\ln@@{1} = 0

ln(1) = 0
Log[1] == 0
Successful Successful - Successful [Tested: 1]
1.2.E1 ( n k ) = n ! ( n - k ) ! k ! binomial 𝑛 𝑘 𝑛 𝑛 𝑘 𝑘 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{n}{k}=\frac{n!}{(n-k)!k!}}}
\binom{n}{k} = \frac{n!}{(n-k)!k!}

binomial(n,k) = (factorial(n))/(factorial(n - k)*factorial(k))
Binomial[n,k] == Divide[(n)!,(n - k)!*(k)!]
Successful Successful - Successful [Tested: 9]
18.35.E4 ( λ - i τ a , b ( θ ) ) n n ! e i n θ F 1 2 ( - n , λ + i τ a , b ( θ ) - n - λ + 1 + i τ a , b ( θ ) ; e - 2 i θ ) = = 0 n ( λ + i τ a , b ( θ ) ) ! ( λ - i τ a , b ( θ ) ) n - ( n - ) ! e i ( n - 2 ) θ Pochhammer 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 𝑛 𝑛 superscript 𝑒 imaginary-unit 𝑛 𝜃 Gauss-hypergeometric-F-as-2F1 𝑛 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 𝑛 𝜆 1 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 superscript 𝑒 2 imaginary-unit 𝜃 superscript subscript 0 𝑛 Pochhammer 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 Pochhammer 𝜆 imaginary-unit subscript 𝜏 𝑎 𝑏 𝜃 𝑛 𝑛 superscript 𝑒 imaginary-unit 𝑛 2 𝜃 {\displaystyle{\displaystyle\frac{{\left(\lambda-\mathrm{i}\tau_{a,b}(\theta)% \right)_{n}}}{n!}e^{\mathrm{i}n\theta}\*{{}_{2}F_{1}}\left({-n,\lambda+\mathrm% {i}\tau_{a,b}(\theta)\atop-n-\lambda+1+\mathrm{i}\tau_{a,b}(\theta)};e^{-2% \mathrm{i}\theta}\right)=\sum_{\ell=0}^{n}\frac{{\left(\lambda+\mathrm{i}\tau_% {a,b}(\theta)\right)_{\ell}}}{\ell!}\frac{{\left(\lambda-\mathrm{i}\tau_{a,b}(% \theta)\right)_{n-\ell}}}{(n-\ell)!}e^{\mathrm{i}(n-2\ell)\theta}}}
\frac{\Pochhammersym{\lambda-\iunit\tau_{a,b}(\theta)}{n}}{n!}e^{\iunit n\theta}\*\genhyperF{2}{1}@@{-n,\lambda+\iunit\tau_{a,b}(\theta)}{-n-\lambda+1+\iunit\tau_{a,b}(\theta)}{e^{-2\iunit\theta}} = \sum_{\ell=0}^{n}\frac{\Pochhammersym{\lambda+\iunit\tau_{a,b}(\theta)}{\ell}}{\ell!}\frac{\Pochhammersym{\lambda-\iunit\tau_{a,b}(\theta)}{n-\ell}}{(n-\ell)!}e^{\iunit(n-2\ell)\theta}
0 < θ , θ < π formulae-sequence 0 𝜃 𝜃 𝜋 {\displaystyle{\displaystyle 0<\theta,\theta<\pi}}
(pochhammer(lambda - I*((a*cos(theta)+ b)/(sin(theta))), n))/(factorial(n))*exp(I*n*theta)* hypergeom([- n , lambda + I*((a*cos(theta)+ b)/(sin(theta)))], [- n - lambda + 1 + I*((a*cos(theta)+ b)/(sin(theta)))], exp(- 2*I*theta)) = sum((pochhammer(lambda + I*((a*cos(theta)+ b)/(sin(theta))), ell))/(factorial(ell))*(pochhammer(lambda - I*((a*cos(theta)+ b)/(sin(theta))), n - ell))/(factorial(n - ell))*exp(I*(n - 2*ell)*theta), ell = 0..n)
Divide[Pochhammer[\[Lambda]- I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]]), n],(n)!]*Exp[I*n*\[Theta]]* HypergeometricPFQ[{- n , \[Lambda]+ I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]])}, {- n - \[Lambda]+ 1 + I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]])}, Exp[- 2*I*\[Theta]]] == Sum[Divide[Pochhammer[\[Lambda]+ I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]]), \[ScriptL]],(\[ScriptL])!]*Divide[Pochhammer[\[Lambda]- I*(Divide[a*Cos[\[Theta]]+ b,Sin[\[Theta]]]), n - \[ScriptL]],(n - \[ScriptL])!]*Exp[I*(n - 2*\[ScriptL])*\[Theta]], {\[ScriptL], 0, n}, GenerateConditions->None]
Error Successful - Successful [Tested: 300]
1.2.E1 n ! ( n - k ) ! k ! = ( n n - k ) 𝑛 𝑛 𝑘 𝑘 binomial 𝑛 𝑛 𝑘 {\displaystyle{\displaystyle\frac{n!}{(n-k)!k!}=\genfrac{(}{)}{0.0pt}{}{n}{n-k% }}}
\frac{n!}{(n-k)!k!} = \binom{n}{n-k}

(factorial(n))/(factorial(n - k)*factorial(k)) = binomial(n,n - k)
Divide[(n)!,(n - k)!*(k)!] == Binomial[n,n - k]
Successful Successful - Successful [Tested: 9]
1.2.E6 ( - 1 ) k ( - z ) k k ! = ( - 1 ) k ( k - z - 1 k ) superscript 1 𝑘 Pochhammer 𝑧 𝑘 𝑘 superscript 1 𝑘 binomial 𝑘 𝑧 1 𝑘 {\displaystyle{\displaystyle\frac{(-1)^{k}{\left(-z\right)_{k}}}{k!}=(-1)^{k}% \genfrac{(}{)}{0.0pt}{}{k-z-1}{k}}}
\frac{(-1)^{k}\Pochhammersym{-z}{k}}{k!} = (-1)^{k}\binom{k-z-1}{k}

((- 1)^(k)* pochhammer(- z, k))/(factorial(k)) = (- 1)^(k)*binomial(k - z - 1,k)
Divide[(- 1)^(k)* Pochhammer[- z, k],(k)!] == (- 1)^(k)*Binomial[k - z - 1,k]
Successful Successful - Successful [Tested: 21]
1.2.E7 ( z + 1 k ) = ( z k ) + ( z k - 1 ) binomial 𝑧 1 𝑘 binomial 𝑧 𝑘 binomial 𝑧 𝑘 1 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{z+1}{k}=\genfrac{(}{)}{0.0% pt}{}{z}{k}+\genfrac{(}{)}{0.0pt}{}{z}{k-1}}}
\binom{z+1}{k} = \binom{z}{k}+\binom{z}{k-1}

binomial(z + 1,k) = binomial(z,k)+binomial(z,k - 1)
Binomial[z + 1,k] == Binomial[z,k]+Binomial[z,k - 1]
Successful Successful - Successful [Tested: 21]
1.2.E8 k = 0 m ( z + k k ) = ( z + m + 1 m ) subscript superscript 𝑚 𝑘 0 binomial 𝑧 𝑘 𝑘 binomial 𝑧 𝑚 1 𝑚 {\displaystyle{\displaystyle\sum^{m}_{k=0}\genfrac{(}{)}{0.0pt}{}{z+k}{k}=% \genfrac{(}{)}{0.0pt}{}{z+m+1}{m}}}
\sum^{m}_{k=0}\binom{z+k}{k} = \binom{z+m+1}{m}

sum(binomial(z + k,k), k = 0..m) = binomial(z + m + 1,m)
Sum[Binomial[z + k,k], {k, 0, m}, GenerateConditions->None] == Binomial[z + m + 1,m]
Successful Successful - Successful [Tested: 21]
1.2.E10 n a + 1 2 n ( n - 1 ) d = 1 2 n ( a + ) 𝑛 𝑎 1 2 𝑛 𝑛 1 𝑑 1 2 𝑛 𝑎 {\displaystyle{\displaystyle na+\tfrac{1}{2}n(n-1)d=\tfrac{1}{2}n(a+\ell)}}
na+\tfrac{1}{2}n(n-1)d = \tfrac{1}{2}n(a+\ell)

n*a +(1)/(2)*n*(n - 1)*d = (1)/(2)*n*(a + ell)
n*a +Divide[1,2]*n*(n - 1)*d == Divide[1,2]*n*(a + \[ScriptL])
Skipped - no semantic math Skipped - no semantic math - -
1.2.E22 M ( r ) = 0 𝑀 𝑟 0 {\displaystyle{\displaystyle M(r)=0}}
M(r) = 0

((p[1]*(a[1])^(r)+ p[2]*(a[2])^(r)+ .. + p[n]*(a[n])^(r))^(1/r)) = 0
((Subscript[p, 1]*(Subscript[a, 1])^(r)+ Subscript[p, 2]*(Subscript[a, 2])^(r)+ \[Ellipsis]+ Subscript[p, n]*(Subscript[a, n])^(r))^(1/r)) == 0
Skipped - no semantic math Skipped - no semantic math - -
1.2#Ex1 M ( 1 ) = A 𝑀 1 𝐴 {\displaystyle{\displaystyle M(1)=A}}
M(1) = A

M(1) = ((a[1]+ a[2]+ .. + a[n])/(n))
M[1] == (Divide[Subscript[a, 1]+ Subscript[a, 2]+ \[Ellipsis]+ Subscript[a, n],n])
Skipped - no semantic math Skipped - no semantic math - -
1.2#Ex2 M ( - 1 ) = H 𝑀 1 𝐻 {\displaystyle{\displaystyle M(-1)=H}}
M(-1) = H

M(- 1) = H
M[- 1] == H
Skipped - no semantic math Skipped - no semantic math - -
1.2.E26 lim r 0 M ( r ) = G subscript 𝑟 0 𝑀 𝑟 𝐺 {\displaystyle{\displaystyle\lim_{r\to 0}M(r)=G}}
\lim_{r\to 0}M(r) = G

limit((p[1]*(a[1])^(r)+ p[2]*(a[2])^(r)+ .. + p[n]*(a[n])^(r))^(1/r), r = 0) = ((a[1]*a[2] .. a[n])^(1/n))
Limit[(Subscript[p, 1]*(Subscript[a, 1])^(r)+ Subscript[p, 2]*(Subscript[a, 2])^(r)+ \[Ellipsis]+ Subscript[p, n]*(Subscript[a, n])^(r))^(1/r), r -> 0, GenerateConditions->None] == ((Subscript[a, 1]*Subscript[a, 2] \[Ellipsis]Subscript[a, n])^(1/n))
Skipped - no semantic math Skipped - no semantic math - -